Amino Acid Transport Assays in Resting Cells of Lactococcus lactis - Hein Trip; Juke Lolkema (Bio-Protocol, 2013)
Many bacteria are auxotrophic for at least a number of amino acids for which they lack the biosynthetic pathways. The organisms are still able to grow in media containing free amino acids as the sole source of amino acid when transport systems for the free amino acids are present in the cytoplasmic membrane. A range of transport systems for essential as well as non-essential amino acids has been described that use the proton motive force (by proton symport) or ATP hydrolysis as driving force to allow for the accumulation of the amino acid in the cells. The most widely used assay for uptake of amino acids (or any other substrate) is the rapid filtration assay using radiolabelled substrates. Here we describe the assay for uptake in resting cells of Lactococcus lactis (L. lactis) that are energized by glucose.